2017
DOI: 10.3390/socsci6010029
|View full text |Cite
|
Sign up to set email alerts
|

Gender in Engineering Departments: Are There Gender Differences in Interruptions of Academic Job Talks?

Abstract: Abstract:We use a case study of job talks in five engineering departments to analyze the under-studied area of gendered barriers to finalists for faculty positions. We focus on one segment of the interview day of short-listed candidates invited to campus: the "job talk", when candidates present their original research to the academic department. We analyze video recordings of 119 job talks across five engineering departments at two Research 1 universities. Specifically, we analyze whether there are differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(104 citation statements)
references
References 45 publications
2
74
0
1
Order By: Relevance
“…For example, the dedication of women-who have children-to their work is perceived to be less than that of their colleagues, including men who also have children (10)(11)(12). Historically underrepresented minorities (HURM) in the United States, Asian/Asian-Americans, and women are all held to stricter competency standards and report having to work harder than Caucasian men to be perceived as legitimate scholars (13,14). Asian/Asian-Americans suffer from imposter syndrome at greater rates than other marginalized groups, and Asian women report a lack of sponsors (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the dedication of women-who have children-to their work is perceived to be less than that of their colleagues, including men who also have children (10)(11)(12). Historically underrepresented minorities (HURM) in the United States, Asian/Asian-Americans, and women are all held to stricter competency standards and report having to work harder than Caucasian men to be perceived as legitimate scholars (13,14). Asian/Asian-Americans suffer from imposter syndrome at greater rates than other marginalized groups, and Asian women report a lack of sponsors (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Other research has shown that faculty are more likely to respond to email requests for graduate mentoring from persons with male, white-sounding names (Milkman et al 2015) and that scientific papers are judged to be of higher quality when attributed to a male author (Knobloch-Westerwick et al 2013). In this volume, Blair-Loy et al (2017) provide new evidence of unequal treatment in the STEM hiring process in the form of videotaped job talks that show more interruptions of women than men candidates for faculty engineering positions.…”
Section: Micro-level Explanationsmentioning
confidence: 99%
“…On the demand side, the most obvious intermediary mechanisms are discrimination against workers and applicants whose gender does not "fit," or align with, the gender of the job, gendered recruitment practices, and biased assessments of individuals' relative qualifications (Becker 1957;Phelps 1980;Bielby and Baron 1986;Foschi 1996;Heilman 2001). On the supply side, stereotyping reinforces segregation by leading people to make gender-conforming choices that affirm their masculinity or femininity, and avoid social sanctions and discriminatory work environments (West and Zimmerman 1987;Ridgeway 2011;Cech 2013;Blair-Loy et al 2017;Weisgram and Diekman 2017).…”
Section: Micro-macro Interactions: Cultural Stereotypes Into Aspirationsmentioning
confidence: 99%
“…Departments have different processes and criteria for selecting invited speakers, but it is a matter of pride to bring the best scientists possible. It may be that the definition of “best” poses a problem to under-represented and under-served groups (e.g., white women, HURM, and Asian) who are held to stricter competency standards and report having to work harder than white men to be perceived as legitimate scholars (32, 33). Some departments only invite tenured faculty, which severely limits the number of potential speakers who are white women or non-Caucasian.…”
Section: Discussionmentioning
confidence: 99%